A three dimensional printed endobronchial stent for the treatment of a broncho-esophageal fistula - Illaa Smesseim; Sophia van Beelen; Jolanda M. van Dieren; Koen J. Hartemink; Johanna van Sandick; Jacobus A. Burgers (Respiratory Medicine Case Reports)
Broncho-esophageal fistulas (BEFs) are a rare but serious complication that can occur after esophagectomy, often resulting in aspiration, respiratory issues, and infection. Management depends on fistula size and location, with options including conservative treatments, surgical closure and stenting. Conventional treatment involves esophageal stents, which may be insufficient for larger or more complex fistulas. This case report describes the first use of a 3D-printed airway stent in combination with an esophageal stent to treat a broncho-esophageal fistula. A 70-year-old patient with distal esophageal adenocarcinoma, treated with neoadjuvant chemoradiation, underwent robot-assisted minimally invasive esophagectomy. The procedure was complicated by a broncho-esophageal fistula, leading to multiple interventions. Despite dual stenting with a custom 3D airway stent, the fistula persisted, and the patient was transitioned to supportive care due to disease progression. This case, the first to use a 3D-printed airway stent for a broncho-esophageal fistula, demonstrates that the stent did not achieve closure, likely due to excessive pressure against the endobronchial wall. This underscores the need for improved 3D stent designs, offering important insights for interventional pulmonologists.